(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
The construction industry faces significant challenges in improving productivity, efficiency, and project quality in the digitalization era. Building Information Modeling (BIM) has emerged as a transformative technology that can change the paradigm of traditional construction project management. This research aims to analyze the development of BIM technology in construction project management through a systematic literature review approach for the period 2021-2025. The research methodology uses the PRISMA 2020 protocol with comprehensive searches on five main academic databases: Scopus, Web of Science, IEEE Xplore, ScienceDirect, and Google Scholar. From the systematic selection process, 10 high-quality articles that met the inclusion criteria were obtained for in-depth analysis using thematic analysis. The research results show that BIM has evolved from a simple design tool to an integrated platform that supports all aspects of construction project management. BIM implementation has been proven to increase project efficiency by up to 30%, reduce construction errors, and optimize time management, cost management, quality management, and risk management. The integration of BIM with emerging technologies such as Artificial Intelligence, Internet of Things, and Machine Learning has created a smart construction site ecosystem that enables real-time monitoring and predictive analysis. However, implementation challenges remain significant, including high initial costs, lack of skilled personnel, and organizational resistance. This research provides theoretical contributions in understanding BIM development trends and practical recommendations for effective implementation in the Indonesian construction industry.